Dehydroepiandrosterone Administration Increased Trabecular Mass and Dihydrotestosterone Levels in the Cancellous Region of the Tibia in Young Female Rats - Park, J.; Aizawa, K.; Akimoto, T.; Iemitsu, M.; Agata, U.; Maeda, S.; Lim, K.; Omi, N. (Hormone and Metabolic Research, 2014)
The aim of the present study was to determine whether dehydroepiandrosterone (DHEA) administration affects bone mass and local sex hormone levels in the cancellous region of young female rats. Eleven female rats (6 weeks old) were randomly divided into 2 groups: control rats (CON, n=5) and rats treated with DHEA (DHEA, n=6). DHEA dissolved in sesame oil was administered to the DHEA group intraperitoneally at 20 mg DHEA/kg body weight, and the CON group was treated with vehicle only (sesame oil, 0.5 ml). The rats were treated with DHEA or vehicle for 3 consecutive days, followed by 1 day of no treatment. The experimental period was 8 weeks. According to dual-energy X-ray absorptiometry and high-resolution microcomputed tomography data, the DHEA group exhibited increased trabecular bone mineral density (BMD), bone volume, and tibial thickness compared to the findings in the CON group, whereas no effect was observed on cortical BMD or morphometry. The concentrations of free testosterone and estradiol in the cancellous region of the tibia did not differ between the 2 groups, but the DHT concentration was significantly higher in the DHEA group than in the CON group. These findings suggest that an increase in local DHT levels may stimulate an increase in trabecular bone mass during growth phases in female rats.
Keywords: DHEA; bone mass; androgen hormones; estrogen-replete state